Gene Knock-Outs of Inositol 1,4,5-Trisphosphate Receptors Types 1 and 2 Result in Perturbation of Cardiogenesis - Uchida, Keiko (Public Library of Science, 2010)
BACKGROUND: Inositol 1,4,5-trisphosphate receptors (IP(3)R1, 2, and 3) are intracellular Ca(2+) release channels that regulate various vital processes. Although the ryanodine receptor type 2, another type of intracellular Ca(2+) release channel, has been shown to play a role in embryonic cardiomyocytes, the functions of the IP(3)Rs in cardiogenesis remain unclear. METHODOLOGY/PRINCIPAL FINDINGS: We found that IP(3)R1(−/−)-IP(3)R2(−/−) double-mutant mice died in utero with developmental defects of the ventricular myocardium and atrioventricular (AV) canal of the heart by embryonic day (E) 11.5, even though no cardiac defect was detectable in IP(3)R1(−/−) or IP(3)R2(−/−) single-mutant mice at this developmental stage. The double-mutant phenotype resembled that of mice deficient for calcineurin/NFATc signaling, and NFATc was inactive in embryonic hearts from the double knockout-mutant mice. The double mutation of IP(3)R1/R2 and pharmacologic inhibition of IP(3)Rs mimicked the phenotype of the AV valve defect that result from the inhibition of calcineurin, and it could be rescued by constitutively active calcineurin. CONCLUSIONS/SIGNIFICANCE: Our results suggest an essential role for IP(3)Rs in cardiogenesis in part through the regulation of calcineurin-NFAT signaling.